Never caught : the story of Ona Judge : George and Martha Washington's courageous slave who dared to run away - Dunbar, Erica Armstrong (Aladdin, 2020)
Explores the life of Ona Judge, one of George and Martha Washington's slaves, who escaped after the Washingtons moved to Philadelphia--the nation's capital at the time--and she began interacting with the city's free black population. Discusses the lengths the Washingtons went to in order to recapture Ona afterwards.